2022
DOI: 10.1037/rel0000421
|View full text |Cite
|
Sign up to set email alerts
|

Zeal of the convert? Comparing religiousness between convert and nonconvert Muslims.

Abstract: In popular culture, converts are thought to be more zealous than those brought up in the same religion (i.e., nonconverts). This is particularly relevant in the context of Islam in Western countries, where outsiders sometimes view conversion to Islam as a harbinger of religious violence rather than a legitimate expression of a search for meaning and truth. However, there is insufficient empirical evidence to suggest that converts believe more strongly and nonconverts. To bridge this gap, this study compares Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Against common public opinion (Pew Research Center, 2009), our results did not support that Muslim converts were more zealous than lifelong believers, which is the second study to find this trend in MLUS converts (following Snook et al, 2021). In fact, MLUS converts had similar scores of maladaptive R/S and lower scores of adaptive R/S.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Against common public opinion (Pew Research Center, 2009), our results did not support that Muslim converts were more zealous than lifelong believers, which is the second study to find this trend in MLUS converts (following Snook et al, 2021). In fact, MLUS converts had similar scores of maladaptive R/S and lower scores of adaptive R/S.…”
Section: Discussioncontrasting
confidence: 93%
“…Research among MLUS converts is similarly unclear, despite their portrayals as zealots in the media. One recent study of MLUS converts found that converts actually had less conviction compared to lifelong believers and in fact struggle more with their faith (Snook et al, 2021). However, other work has demonstrated that some MLUS experience intense and notable shifts in R/S after conversion that are associated with better mental health outcomes (Wilkinson et al, 2021), and that these shifts lead to a greater identification with Islam and a deep sense of meaning (Bowen, 2009;La Voie, 2017;Maslim & Bjorck, 2009).…”
Section: The Zeal Of a Convertmentioning
confidence: 99%
“…The notion of the "convert's zeal" in the Islamic context is further problematized by Snook et al (2020), whose comparative analysis of religiousness between American Muslim converts and non-converts "directly contradict the idea that U.S. Muslim converts are especially zealous," with converts exhibiting lower levels of religiousness across a range of variables compared to non-converts. The authors also caution against blind acceptance of the "convert's zeal" theory, asserting that "speculation about this phenomenon has made converting to Islam an even more stigmatizing and marginalizing process" (2021,4).…”
Section: Conversion To Islam and Extremismmentioning
confidence: 99%
“…(KR, interview) In socio-reality, it is acknowledged that there seem to be different religious practices between the born Muslims and Muslim convert. Snook has made this phenomenon clearly explained, his study on the structure of Islamic practices between born-Muslim and Muslim convert revealed that there is a meaningful difference in the way that converts have-they perform more simple structure of practice than the born-Muslims (Snook, 2019). Conclusively, born-Muslims and Muslim converts believe then practice Islam in different structure.…”
Section: A Stigma From Inner-circlementioning
confidence: 99%